Grado del cumplimiento de medidas de ecoeficiencia en el personal administrativo de la Municipalidad Distrital de Punchana. Loreto. 2024 - Pereira Pinedo, Julio Gabriel (2024)
This research work was developed in the district municipality of Punchana, and its objective was to determine the degree of compliance with eco-efficiency standards in the administrative workers of the district municipality of Punchana in 2023. The research, due to its approach, was quantitative, prospective, and of a descriptive comparative research level and non-experimental research design. The research included the participation of 71 administrative workers from the administrative areas of administration, treasury, and accounting, who were present during the application of the data collection instrument. The survey technique was used and a questionnaire was applied divided by dimensions of electric energy, solid waste, and use of paper and related materials, extracted from the eco-efficiency standards issued by the MINAM. The main results expressed that there is a significant commitment to eco efficiency standards in the use of electric energy, although there is still a considerable portion of workers who do not comply with them consistently. There is also a positive trend towards compliance with eco-efficiency regulations in solid waste management, with a majority of workers committed, although there are still areas of opportunity to reduce the percentages of non-compliance and to comply with eco-efficiency regulations in the use of paper and related materials, which reflects a positive level of commitment and in general the Student t test showed a lack of statistical significance in the degree of compliance in eco-efficiency between administrative areas